Estresse oxidativo sistêmico em cães com doença periodontal - Matono, Daniela [UNESP] (2015)
Periodontal disease (PD) is the most common disease of the oral cavity in dogs is inflammatory, chronic and infectious and is responsible for the production of reactive species of oxygen (ROS). Excessive ROS can lead to the situation known as oxidative stress, or imbalance of oxidants and antioxidants. Systematic review was performed on PD and oxidative stress to investigate the hypothesis that the canine PD suffers oxidative stress and this varies with the degree of the disease. To this end, we selected 22 dogs with PD, all adults, of different races and genders. The control group was made up of the same dogs, 30 days after periodontal treatment, all without any changes in physical and laboratorial examination. To evaluate oxidative stress was measured the full blood antioxidant capacity (TAC), plasma antioxidant, the total concentration of plasma oxidant (OCD), oxidative stress index, oxidative metabolism of circulating neutrophils (superoxide production by cytochemical test of reduction of nitroblue tetrazolium - NBT) and plasma lipid peroxidation (concentration of thiobarbituric reactive species - TBARS). Studies linking oxidative stress and PD are still rare in dogs, and humans with periodontitis has more oxidative stress compared to the control group. Oxidative stress in dogs PD was confirmed in peridontites (TAC decrease and increased neutrophil superoxide production), but these changes did not differ as to the degree of injury and were not significant in gingivitis. This is probably the first evidence that systemic oxidative stress occurs in canine periodontitis and that neutrophils